E-Tourism as A Promotion Media for Cimande Tourism Village - Sari, Dhanik Puspita; Batubara, Rima Pratiwi (E-Journal of Tourism, 2021)
Cimande Tourism Village promotion is done to provide information to potential visitors about the tourism potential in the region. Promotion using the website (e-tourism) is believed to convey information more clearly and widely. This research was conducted in Cimande Tourism Village, in Caringin District, Bogor Regency. Research uses qualitative descriptive methods. The research object is Cimande tourism village website’s with access desawisatacimande.com. The result discover that Cimande tourism village website has a fairly good level of visibility by using search engines namely Google, Yahoo and Bing. Promotional techniques are carried out by linking information related to tourism, namely information about the activities of Cimande Tourism Village itself. Online public relations not yet available. The websites email are available even though they are still minimal in use. The manager has not recorded the visitors so the ranking related to the visitor does not exist. Therefore, the author recommends that managers work together with other institutions to meet human resources needs in order to improving knowledge and skills related to the promotion, especially for websites. In addition, the manager can also ask the relevant institutions to cooperate in the promotion activities of Cimande Tourism Village.